Course of vitamin D levels before and after liver transplantation in pediatric patients. (2nd June 2021) - Yuksel, Muhammed; Demir, Bariş; Mizikoğlu, Özlem; Akyildiz, Murat; Baygul, Arzu; Arikan, Cigdem
Abstract: Background: 25‐hydroxy VD insufficiency is known in children undergoing LT but the serial post‐transplant VD course and supplementation modalities in the peri‐transplant period are lacking. We aimed to determine the pre‐VD status and the post‐transplant VD status course following VD supplementation and to elucidate its relationship with post‐transplant outcome parameters such as infection and survival. Methods: Pre‐ and post‐VD levels were monitored in parallel with interventions to adjust VD levels in LT patients. VD status was categorized as circulating levels <30–21 ng/ml (insufficiency), 20–10 ng/ml (deficiency), and <10 ng/ml (severe deficiency). Patients received stoss (300000IU) VD3 within the pretransplant period if serum levels were <20 ng/ml. Results: 135 transplanted children were included. The age at LT was 22 months (IQR: 8–60). The pretransplant median VD level was 14 ng/ml. Despite stoss dose, post‐transplant median VD level was 1.8 ng/ml (day one), 4 ng/ml (week one), 19 ng/ml (month one), 33 ng/ml (month three), 38 ng/ml (months 6–12), and 40 ng/ml (month 24). After 6 months, VD status reached >30 ng/ml in 98% of patients. Only at pre‐LT, higher infection rate (18.7%) in the severe VD deficiency group was observed compared to the VD deficiency group (2.9%, p = .04). Survival was not affected by serum VD levels. Conclusion: VD levels fell substantially after LT but are rectifiable by stoss dose, which was well tolerated. Only the infection rate was associated with the VD status.